COMMUNITY-BASED ACTION PLANS FOR COASTAL AREA INFRASTRUCTURE ENHANCEMENT: A STRATEGY FOR SUSTAINABLE TOURISM DEVELOPMENT - Pratama, Ferdianta Wahyu Nur; Jannah, Mutia Raudatul (ipdn, 2024)
Coastal areas, as a transition between terrestrial and marine ecosystems, have significant potential for regional development, particularly in the tourism sector. Settlements in these areas are rapidly expanding, posing severe challenges, including the emergence of slum areas. Sustainable development fully involves community participation and creates resilience for communities and cities facing future threats. The purpose of this article is to conceptualize the improvement of settlement infrastructure in fishing villages based on community empowerment. Literature review and analysis of planning documents are the methods used to achieve the article's objectives. Holistic and participatory planning is vital to improving the quality of infrastructure in coastal settlements. Development involving all components of the local community and cooperation from the private sector is expected to create integrated coastal areas that combine housing, infrastructure, and tourism potential. This approach is expected to create more resilient and sustainable fishing villages.Keywords: Coastal Area, Slum area, Community Empowerment, Tourism Development